The nickel-chelator dimethylglyoxime inhibits human amyloid beta peptide in vitro aggregation - Stéphane L. Benoit (Nature Portfolio, 2021)
Abstract One of the hallmarks of the most common neurodegenerative disease, Alzheimer’s disease (AD), is the extracellular deposition and aggregation of Amyloid Beta (Aβ)-peptides in the brain. Previous studies have shown that select metal ions, most specifically copper (Cu) and zinc (Zn) ions, have a synergistic effect on the aggregation of Aβ-peptides. In the present study, inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the metal content of a commercial recombinant human Aβ40 peptide. Cu and Zn were among the metals detected; unexpectedly, nickel (Ni) was one of the most abundant elements. Using a fluorescence-based assay, we found that Aβ40 peptide in vitro aggregation was enhanced by addition of Zn2+ and Ni2+, and Ni2+-induced aggregation was facilitated by acidic conditions. Nickel binding to Aβ40 peptide was confirmed by isothermal titration calorimetry. Addition of the Ni-specific chelator dimethylglyoxime (DMG) inhibited Aβ40 aggregation in absence of added metal, as well as in presence of Cu2+ and Ni2+, but not in presence of Zn2+. Finally, mass spectrometry analysis revealed that DMG can coordinate Cu or Ni, but not Fe, Se or Zn. Taken together, our results indicate that Ni2+ ions enhance, whereas nickel chelation inhibits, Aβ peptide in vitro aggregation. Hence, DMG-mediated Ni-chelation constitutes a promising approach towards inhibiting or slowing down Aβ40 aggregation.